2017
DOI: 10.1175/jcli-d-17-0328.1
|View full text |Cite
|
Sign up to set email alerts
|

Widening of the Hadley Cell from Last Glacial Maximum to Future Climate

Abstract: The Hadley cell (HC) change from paleoclimate to future climate is examined by comparing coupled model simulations archived for the Paleoclimate Modeling Intercomparison Project phase 3 (PMIP3) and phase 5 of the Coupled Model Intercomparison Project (CMIP5). Specifically, HC width and strength are evaluated using 100-yr equilibrium simulations for the Last Glacial Maximum (LGM), preindustrial (PI), and extended concentration pathway 4.5 (ECP4.5) conditions. Where available, ECP8.5 simulations are also examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 49 publications
8
33
0
Order By: Relevance
“…As discussed in section 1, under increased GHG the stabilization of the subtropics (the increase in static stability) is responsible for the poleward shift of the HC (e.g., Lu et al, ; Son et al, ). The subtropical (averaged between 30°S–40°S and 400–800 mb) static stability, N=()gθ∂θ∂z12 (where θ is potential temperature and z is height), indeed shows a larger increase in the SOM than in the FOM ( δ N , Figure b), in agreement with a larger HC expansion in the SOM than in the FOM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in section 1, under increased GHG the stabilization of the subtropics (the increase in static stability) is responsible for the poleward shift of the HC (e.g., Lu et al, ; Son et al, ). The subtropical (averaged between 30°S–40°S and 400–800 mb) static stability, N=()gθ∂θ∂z12 (where θ is potential temperature and z is height), indeed shows a larger increase in the SOM than in the FOM ( δ N , Figure b), in agreement with a larger HC expansion in the SOM than in the FOM.…”
Section: Resultsmentioning
confidence: 99%
“…(ii) Regarding the HC's meridional width, it was found to follow the latitude where the angular momentum conserving flow becomes baroclinically unstable (Held, ). Under increased GHG, the stabilization of the subtropics and its associated reduction in baroclinicity were found to shift the HC edge poleward (Lu et al, ; Son et al, ). (iii) Regarding the circulation's height, from radiative considerations alone, the height of the tropical tropopause is expected to increase, due to both a reduction in the temperature lapse rate and an increase in surface temperature (Thuburn & Craig, , ; Vallis et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, while enhanced greenhouse gas emissions were found to expand the tropical circulation in recent decades (e.g., Bony et al 2013;Hu et al 2013), the buildup of anthropogenic aerosols in the Northern Hemisphere were found to contract the circulation, and thus offset the expansion signal (Allen and Ajoku 2016). In the Southern Hemisphere, ozone depletion was found to be the main forcing of tropical expansion in the second half of the twentieth century (Son et al 2009;Polvani et al 2011b), and the ongoing recovery of ozone hole will therefore cancel the effect of greenhouse gases throughout the first half of the twenty-first century (Polvani et al 2011a; Barnes et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A significant body of work has examined the expansion of the Hadley cell under global warming in both observations and numerical simulations (see recent reviews, Grise et al, 2019;Staten et al, 2018). However, the extent of the Hadley cell is also sensitive to natural variability of sea surface temperatures (SSTs; Grassi et al, 2012;Lu et al, 2008), anthropogenic emission of aerosols (Allen & Sherwood, 2011), and ozone depletion (Son et al, 2008). Furthermore, the Southern and Northern Hemispheres may respond differently to each of these forcings.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial ozone loss in the Southern Hemisphere polar vortex has occurred during spring, which has driven lower polar stratospheric temperature and hence accelerated zonal winds. In turn, the eddy-driven jet in the Southern Hemisphere has shifted poleward due to this ozone loss (primarily in summer) and this has driven a portion of the Hadley cell expansion in the Southern Hemisphere during the observed record (McLandress et al, 2011;Son et al, 2008;Thompson & Solomon, 2002). In the Northern Hemisphere there has been comparatively little ozone loss, and for this reason, asymmetries in simulated Hadley cell expansion between the Southern and Northern Hemispheres are often attributed to the impacts of ozone-depleting substances onto the atmospheric circulation.…”
Section: Introductionmentioning
confidence: 99%